Effect of Inquiry Learning and Culturally Responsive Teaching and Mathematical Problem Solving - Wiska Adhwaa Budiarsih; Hetty Patmawati; Sri Tirto Madawistama (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The low level of students’ mathematical problem-solving ability remains a major issue in mathematics learning, particularly when instructional practices fail to actively engage students and to integrate cultural contexts relevant to their daily lives. This study was motivated by the limited integration of the Inquiry Learning Model with the Culturally Responsive Teaching (CRT) approach, especially within Islamic boarding school settings, and by the suboptimal achievement in solving problems related to the System of Linear Equations in Three Variables. This research aimed to examine (1) whether there is a significant effect of the Inquiry Learning Model integrated with CRT on students’ mathematical problem-solving ability, and (2) the magnitude of such an effect. A quasi-experimental method with a posttest-only control group design was employed. The population consisted of all tenth-grade female students of SMA Terpadu Riyadlul ‘Ulum in the 2025/2026 academic year. Samples were selected through purposive sampling and cluster random sampling, resulting in class X-1 as the experimental group and class X-4 as the control group. The instrument was an essay test constructed based on Polya’s four problem-solving indicators and validated by experts. Data were analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, Independent Samples t-test, and coefficient of determination. The findings revealed a significant difference between the experimental and control groups (p = 0.000 < 0.05). The coefficient of determination (R² = 0.436) indicates that 43.6% of the variance in mathematical problem-solving ability was explained by the applied learning model, which falls into a moderate effect category. Thus, the integration of the Inquiry Learning Model with the CRT approach significantly enhances students’ mathematical problem-solving ability and is recommended as an effective contextual learning alternative in mathematics education.